2x+18+1-1 works if that's all you want
I think, the answer will be -7
We have:
f(x)=1/(x-2)
g(x)
Then:
(fg)(x)=[1/(x-2)](g(x))=g(x)/(x-2)
Now; we calculate: (fg)`(x)
Remember: (u/v)=(u`v-vu´)/v²
Therefore:
(fg)´(x)=[g´(x)*(x-2) - 1*g(x)]/ (x-2)²
We know that:
g´(1)=-1
(fg)´(1)=6
Therefore:
6=[-1*(1-2)-g(1)]/(1-2)²
6=[1-g(1)]/1
6=1-g(1)
-g(1)=6-1
g(1)=-5
Answer: B. -5
Answer:
x = 7.5y
Step-by-step explanation:
Simplifying
4.2(2x + -0.5y) + -2(4.1x + -0.3y) = 0
(2x * 4.2 + -0.5y * 4.2) + -2(4.1x + -0.3y) = 0
(8.4x + -2.1y) + -2(4.1x + -0.3y) = 0
8.4x + -2.1y + (4.1x * -2 + -0.3y * -2) = 0
8.4x + -2.1y + (-8.2x + 0.6y) = 0
Reorder the terms:
8.4x + -8.2x + -2.1y + 0.6y = 0
Combine like terms: 8.4x + -8.2x = 0.2x
0.2x + -2.1y + 0.6y = 0
Combine like terms: -2.1y + 0.6y = -1.5y
0.2x + -1.5y = 0
Solving
0.2x + -1.5y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '1.5y' to each side of the equation.
0.2x + -1.5y + 1.5y = 0 + 1.5y
Combine like terms: -1.5y + 1.5y = 0.0
0.2x + 0.0 = 0 + 1.5y
0.2x = 0 + 1.5y
Remove the zero:
0.2x = 1.5y
Divide each side by '0.2'.
x = 7.5y
Simplifying
x = 7.5y
Answer: d = -9/8
Steps: 5d + ½ = d - 4
Subtract ½ from both sides: 5d + ½ - ½ = d - 4 - ½
Simplify: 5d = d - 9/2
Subtract d from both sides: 5d - d = d - 9/2 - d
Simplify: 4d = -9/2 ÷ 4
Simplify: d = -9/8
PLz mark brainliest:)
Answer:
hm
Step-by-step explanation:
and then I say no one knows where I I am to find it and then he